Robert von Hallberg, ed.: Literary Intellectuals and the Dissolution of the State. Professionalism and Conformity in the GDR - Kristie A Foell (GDR Bulletin, 1999)
Kenneth J. Northcott, trans. Chicago: University of Chicago Press, 1996. 366 p.